Attenuation of autonomic dysreflexia during functional electrical stimulation cycling by neuromuscular electrical stimulation training: case reports - Gill, Satinder (Spinal Cord Ser Cases, 2020)
INTRODUCTION: Spinal cord injury (SCI) may cause impairments of the motor, sensory, and autonomic nervous systems, which result in adverse changes in body composition and cardiovascular health. Functional electrical stimulation (FES) cycling may provide an effective alternative approach to perform exercise and improve cardiovascular health after SCI. Persons with an injury at or above T6 level are at high risk of developing a life-threatening complication of autonomic dysreflexia (AD). CASE PRESENTATION: Two participants with motor-complete C6 SCI completed either 12 weeks of passive range of motion or surface neuromuscular electrical stimulation (NMES) resistance training, followed by 12 weeks of functional electrical stimulation (FES) lower extremity cycling for both participants. Systolic and diastolic blood pressure (BP) were measured to determine the effects of NMES-resistance training and FES-lower extremity cycling during rest and exercise. DISCUSSION: The difference between mean value of BP during FES-lower extremity cycling exercise and resting BP averaged for 24 sessions was smaller for participant A (31.25 mmHg for systolic BP and 10.44 mmHg for diastolic BP), who received NMES-resistance training, as compared with participant B (58.62 mmHg for systolic BP and 35.07 mmHg for diastolic BP). The results of these case reports suggest that 12 weeks of NMES-resistance training preceding FES-lower extremity cycling may attenuate the development of AD after SCI. Risk of AD, triggered by noxious stimuli, may be dampened with FES-lower extremity cycling training in persons with SCI.